Effect of Endometrial Injury on Secretion of Endometrial Cytokines and IVF Outcomes in Women with Unexplained Subfertility - Yu Liang; Junyan Han; Chanwei Jia; Yanmin Ma; Yonglian Lan; Ying Li; Shuyu Wang (Hindawi Limited, 2015)
In order to determine the effect of endometrial injury (EI) on in vitro fertilization (IVF) outcomes in women with unexplained subfertility and explore the relationship between EI and endometrial inflammatory cytokines, 66 women with unexplained subfertility undergoing IVF treatment were recruited. 38 patients in the EI group underwent EI in the mid-luteal phase of the cycle and 28 patients in the non-EI (NEI) group. According to the pregnancy outcome, the NEI and EI groups were divided into NEI-nonpregnant (NEI-NP), NEI-pregnant (NEI-P), EI-NP, and EI-P. All patients underwent aspiration of endometrial secretions immediately before embryo transfer. The concentrations of ten mediators were measured using Milliplex Magnetic Bead assay. The clinical pregnancy was significantly higher in the EI than in the NEI group. The concentrations of interleukin- (IL-) 6, IL-8, IL-12 (p70), IL-13, interferon- (IFN-) γ, monocyte chemotactic protein- (MCP-) 1, and vascular endothelial growth factor (VEGF) were significantly higher in the EI than the NEI group. The expression of IFN-γ and VEGF in the EI-P was significantly increased compared to the EI-NP group. These findings suggest that, in women with unexplained subfertility, endometrial injury might be a potential method to improve clinical pregnancy rates by promoting the expression of IFN-γ and VEGF.